Analisis Kelayakan Ekonomi Tambang Batu Andesit Menggunakan Metode Discounted Cash Flow PT. Ansar Terang Crushindo Site Atc 1 Kecamatan Pangkalan Koto Baru, Sumatera Barat. - Ainil Khalisah; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. PT. Ansar Terang Crushindo site Atc 1 is a company that conducts andesite mining which has 10.899.982 tons of andesite reserves and 20 years of mine life. The parameters for this research can be seen in terms of economics, needs for tools’ estimation, and the income from the andesite selling. Then investment analysis and economics appropriateness of the mine are needed to see the prospect of andesite reserves whether they have economic value in the location. The parameters used to determine the economics appropriateness in the production of andesite at PT. Ansar Terang Crushindo site Atc 1 is Net Present Value (NPV), Internal Rate Return (IRR), and Payback Period (PP). Based on the result of economics analysis research, it was obtained the Net Present Value Rp. 1.794.057.062.400,, Internal Rate Return 41%, and Payback Period of 2,8 years, so the project is worthy to run. The estimated equipment needs are 1 unit of Komatsu PC 400 Excavator, and 4 Mitsubishi Fuso 250 PS FN 627 40T Dump Truck to overburden removal, and for ore getting requires 1 Komatsu PC 300 Excavator and 3 units of Mitsubishi Fuso 250 PS FN 627 40T. The income from the andesite selling was Rp. 1.080.000.000.000. Keywords: Analisis investasi, econimic feasibility, estimation of tool requirements, NPV, IRR, PBP, andesite stone sales.